Stability study of royal jelly in alginate-pectin beads - Azhar, Muhammad Fitri; Mohammad Hamdi, Nurul Ain; Haris @ Harith, Muhammad Salahuddin (IIUM Press, 2023)
The stability of royal jelly (RJ) beads is a critical aspect to ensure the product is safe, efficacious, and possesses an acceptable quality for consumers. This study aims to establish storage duration and condition to ensure the stability of RJ in alginate-pectin beads